2002
DOI: 10.1046/j.1439-0418.2002.00603.x
|View full text |Cite
|
Sign up to set email alerts
|

Predatory effect of Orius niger (Wolff) (Hem., Anthocoridae) on Frankliniella occidentalis (Pergande) and Thrips tabaci Lindeman (Thysan., Thripidae)

Abstract: The predatory effect of adult female Orius niger (Wolff) (Hem., Anthocoridae) on the larvae I–II and adults of two injurious thrips, Frankliniella occidentalis (Pergande) and Thrips tabaci Lindeman (Thysan., Thripidae), was examined in June 1997, in controlled environment chambers (temperature 22 ± 0.2°C, 65 ± 3% RH, a 16 h light : 8 h dark photoperiod and light intensity 9000 Lux). This study took place on sweet pepper leaves (Capsicum annuum L.) in transparent small plastic cages at proportions of 1/5, 1/10,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
1
12
0
3
Order By: Relevance
“…Also, the analysis of the nymphal development time, nymphal mortality percentage, pre-oviposition, and oviposition period indicated that the population growth of O. niger was restricted mostly by a high nymphal mortality, low sex ratio, and low r m when fed female mites, and the population growth of O. minutus was Few studies address the intrinsic rate of natural increase for O. niger and O. minutus when fed OT and TSSM. Deligeorgidis (2002) demonstrated that O. niger strongly preferred 2nd instar larvae of OT when compared with the 2nd instar larvae of F. occidentalis, and concluded that O. niger was a suitable predator to control OT. Baniameri et al (2005) estimated a high r m (0.113) for O. niger at 26°C on a diet of E. kuehniella eggs and suggested that the population growth rate of O. niger was restricted mostly by juvenile mortality.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Also, the analysis of the nymphal development time, nymphal mortality percentage, pre-oviposition, and oviposition period indicated that the population growth of O. niger was restricted mostly by a high nymphal mortality, low sex ratio, and low r m when fed female mites, and the population growth of O. minutus was Few studies address the intrinsic rate of natural increase for O. niger and O. minutus when fed OT and TSSM. Deligeorgidis (2002) demonstrated that O. niger strongly preferred 2nd instar larvae of OT when compared with the 2nd instar larvae of F. occidentalis, and concluded that O. niger was a suitable predator to control OT. Baniameri et al (2005) estimated a high r m (0.113) for O. niger at 26°C on a diet of E. kuehniella eggs and suggested that the population growth rate of O. niger was restricted mostly by juvenile mortality.…”
Section: Discussionmentioning
confidence: 98%
“…Yano et al (2002) mentioned that the use of indigenous predator species is preferable to the use of imported species. The longevity and fecundity of Orius species vary according to the consumed prey species (Kiman and Yeargan 1985;Venzon et al 2001Venzon et al , 2002Deligeorgidis 2002). The purpose of this research was to (a) identify the dominant anthocorid species in potato Welds infested with OT and TSSM, (b) determine the relationship between the densities of the dominant species of anthocorid and OT and TSSM, and (c) study the life table parameters of Orius niger (WolV) and O. minutus (Linnaeus) when fed OT and TSSM on potato leaves.…”
Section: Introductionmentioning
confidence: 99%
“…Gitonga et al (2002) found that adult M. sjostedti are more mobile than the larvae, and thus may escape attack by the predators, thereby resulting in more larvae being attacked at all the temperatures and densities. Deligeorgidis (2002) demonstrated that O. niger strongly preferred second instar larvae of Thrips tabaci compared to the second instar larvae of Frankliniella occidentalis, and concluded that O. niger was a suitable predator to control onion thrips. Toyoshima (2006) reported that O. minutus had the potential to control mite populations on apple trees in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the Orius species consumed 5.5-29.1 F. occidentalis larvae per day. Deligeorgidis (2002) found O. niger to be an effective control agent of F. occidentalis, where it consumed 15 larvae/day in 24 h. The mirid bug, D. tamaninii, consumed 23.5 thrips larvae in the present experiments, which was more than the 10.9-12.7 nymphs consumed per day recorded by Riudavets and Castan˜e´(1998). This difference could be due to the fact that different experimental conditions and prey stages were used in the present and earlier experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Macrolophus pygmaeus (Rambur) (Heteroptera: Miridae), another predatory bug, has also shown good results against whiteflies (Aleyrodidae), aphids (Aphididae) and mites (Tetranychidae), especially in the presence of other natural control factors, like parasitoids and predatory mites (Perdikis and Lykouressis 2000;Lykouressis et al 2001;Hillert et al 2002). Orius niger (Wolff) (Heteroptera: Anthocoridae) was tested for the biological control of F. occidentalis and T. tabaci (Van de Veire and Degheele 1992; Dissevelt et al 1995;Deligeorgidis 2002). The results, however, showed little success of this natural enemy against these two pest species.…”
Section: Introductionmentioning
confidence: 99%